PERSPEKTIF FUTURISTIK PANCASILA SEBAGAI ASAS/IDEOLOGI DALAM UU KEORMASAN - Ibrahim, Anis (Jurnal Konstitusi, 2010)
The 1983 law on mass organization states that each mass organization shall use Pancasila as the only organization basis is not effective anymore. This ineffectiveness is due to the silence in talking about Pancasila under perspective in solving the problems of the nation and to the reluctance of the government to enforce Pancasila as the only basis for mass organizations. Therefore, it is time to amend it by adopting the 2008 law on political parties, especially those dealing with the position of Pancasila as a basis that enables mass organizations to adopt other basis with stipulation that the  adopted basis should not be in contradiction to the Pancasila ideology